Limitation by nesting habitat of the density of breeding Ringed Plovers Charadrius hiaticula: a natural experiment - Pienkowski, M W; Pienkowski, A E (Wildfowl, 1989)
Some previously stony nesting areas of Ringed Plovers at Lindisfarne, Northumberland, became covered by sand over about ten years whilst feeding areas remained at least as suitable. Breeding numbers declined in changed areas but remained more constant in others. Densities in new sandy areas became similar to those sandy throughout the period. This is discussed in relation to adaptations to breeding habitat, and with respect to conservation implications.